Ultra-Sensitive Serial Profiling of SARS-CoV-2 Antigens and Antibodies in Plasma to Understand Disease Progression in COVID-19 Patients with Severe Disease. (30th November 2020) - Ogata, Alana F; Maley, Adam M; Wu, Connie; Gilboa, Tal; Norman, Maia; Lazarovits, Roey; Mao, Chih-Ping; Newton, Gail; Chang, Matthew; Nguyen, Katrina; Kamkaew, Maliwan; Zhu, Quan; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has infected over 21 million people worldwide since August 16, 2020. Compared to PCR and serology tests, SARS-CoV-2 antigen assays are underdeveloped, despite their potential to identify active infection and monitor disease progression. Methods: We used Single Molecule Array (Simoa) assays to quantitatively detect SARS-CoV-2 spike, S1 subunit, and nucleocapsid antigens in the plasma of patients with coronavirus disease (COVID-19). We studied plasma from 64 patients who were COVID-19 positive, 17 who were COVID-19 negative, and 34 prepandemic patients. Combined with Simoa anti-SARS-CoV-2 serological assays, we quantified changes in 31 SARS-CoV-2 biomarkers in 272 longitudinal plasma samples obtained for 39 patients with COVID-19. Data were analyzed by hierarchical clustering and were compared to longitudinal RT-PCR test results and clinical outcomes. Results: SARS-CoV-2 S1 and N antigens were detectable in 41 out of 64 COVID-19 positive patients. In these patients, full antigen clearance in plasma was observed a mean ± 95% CI of 5 ± 1 days after seroconversion and nasopharyngeal RT-PCR tests reported positive results for 15 ± 5 days after viral-antigen clearance. Correlation between patients with high concentrations of S1 antigen and ICU admission (77%) and time to intubation (within 1 day) was statistically significant. Conclusions: The reported SARS-CoV-2 Simoa antigen assay is the first to detect viral antigens in the plasma of patients who were COVID-19 positive to date. These data show that SARS-CoV-2 viral antigens in the blood are associated with disease progression, such as respiratory failure, in COVID-19 cases with severe disease.